Philosophy in technology: A research program - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
Philosophy in technology is a research program that studies the philosophical roots of engineering and technology. Technologists, by virtue of their education, believe that the limits, goals, possibilities, and effects of technology on society and humankind are exclusively technological problems, hence their solutions must lie exclusively in technology. In contrast, philosophy in technology asserts that the resolutions to these problems need to be rooted in an understanding of their philosophical origins. This program paper defines the objectives of philosophy in technology, the kinds of questions it explores, the methods it uses, and how it differs from the philosophy of technology.